The effects of Dzyaloshinskii-Moriya interactions on the ferromagnetic resonance response in nanosized devices - Eason, Kwaku (2014)
The effects of Dzyaloshinskii-Moriya interaction (DMI) on the ferromagnetic resonance response are investigated in nanometer-sized disks using 3D micromagnetics with the inclusion of DMI energy. A rich complexity is found in the effects on the spinwave eigenmodes and their behavior when varying parameters. Two distinct results are demonstrated: first, unique DMI modes are found to form, instead of the expected modes forming in the absence of DMI and they can be uniquely accessed using field rotation; and second, modal evolution with the DMI parameter involves distinct modal twisting and rotations.